Upaya Meningkatkan Karakter Tanggung Jawab Melalui Pembiasaan Pada Peserta Didik Kelas I SD Negeri Kragilan Tahun 2021/2022 - Adiana Septianicha; Anita Trisiana; Ratna Widyaningrum (Journal on Education, 2022)
The purpose of this study was to determine the improvement in the character of the students' responsibilities by applying the habituation method to class I students. This research was conducted at SD Negeri Kragilan, Boyolali Regency. The subjects in this study were class I students, totaling 7 students. This research is a Classroom Action Research (PTK) which is carried out in 3 cycles. The data analysis technique used is descriptive comparative which can describe and compare the results of the initial conditions, cycle I and cycle II. The validity of the data used is the triangulation method, which checks the degree of discovery of research results using several methods, namely observation, interviews, questionnaires and documentation. Based on the results of the study it was concluded that through habituation it can improve the character of responsibility of class I students as evidenced through the results of research on the character of responsibility with an average value of aspects during the pre-cycle of 62.85%, cycle I 75.53%, cycle II 81.42%, cycle III 82.67%.